(3GdbGehS GdeMjW hGdbCHhS GdhSjWs - (3eMeO Hf jYbhH Hf eMeO, eLO GdOjf GdajQhRGHGOj,J (B817 (3g` s
(3ChdgG (B:s
(3ef aUd GdMGA GdegedI ef HGH GdHGA , GdMhCH cchcH , Ke CTGQ HhRfg Edi RjGOI GdhGh hbjd GdhGh CUdjI , hGdgeRI gi GdRGFOI hYdjg ajPcQ ai M h H ceG ai GdUMGM s
(3BNQgG (B:s
(3ef aUd GdjGA GdJMJjI BNQ GdMQha , eGOI jQL , hgh fgGjI HGH GdLje bhdg (B: (3hbGd GHf SjOg ai GdeMce GdjGRL ef Mdi GdjOjf , aGQSi bdJ (B: (3hcCfg de jYQH hChQO CcKQ efGaYgG hTQM daXgG OGhO ai GdJPcQg , hZjQ hGMO GfJgi HGH GdLje GfJgi GdfUa GdChds
(3GdLRA GdKGfi ef GdfSNI GdSGHbI faSgGs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B147s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B2 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GddZIs